2017
DOI: 10.1007/s10652-017-9513-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the secondary motions on pollutant mixing in a meandering open channel flow

Abstract: This paper presents large eddy simulation of turbulent flow in a meandering open channel with smooth wall and rectangular cross-section. The Reynolds number based on the channel height is 40,000 and the aspect ratio of the cross-section is 4.48. The depth-averaged mean stream-wise velocity agree well to experimental measurements. In this specific case, two interacting cells are formed that swap from one bend to the other. Transport and mixing of a pollutant is analysed using three different positions of releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…The subgrid-scale (SGS) stresses, resulting from the unresolved motions, are modelled using the Smagorinsky subgrid-scale model (Smagorinsky, 1963) with a model constant Cs of 0.1. Such an approach has been used successfully for similar flows by Hinterberger et al (2007) and Moncho-Esteve et al (2017). For flows without homogeneous directions, as the present one, the Smagorinsky model is more robust than other models like the dynamic Smagorinsky which require some kind of smoothing of the model parameter (like time relaxation).…”
Section: Numerical Methods and Computational Setupmentioning
confidence: 74%
See 1 more Smart Citation
“…The subgrid-scale (SGS) stresses, resulting from the unresolved motions, are modelled using the Smagorinsky subgrid-scale model (Smagorinsky, 1963) with a model constant Cs of 0.1. Such an approach has been used successfully for similar flows by Hinterberger et al (2007) and Moncho-Esteve et al (2017). For flows without homogeneous directions, as the present one, the Smagorinsky model is more robust than other models like the dynamic Smagorinsky which require some kind of smoothing of the model parameter (like time relaxation).…”
Section: Numerical Methods and Computational Setupmentioning
confidence: 74%
“…With respect to modelling, in the literature there are several Reynolds-averaged Navier-Stokes (RANS) studies of flow in compound meandering channels (Morvan et al, 2002;De Marchis and Napoli, 2008;Shukla and Shiono, 2008;Jing et al, 2009). However, Van Balen et al (2010), Constantinescu et al (2013) and Moncho-Esteve et al (2017) have shown that, generally, Large Eddy Simulation (LES) provides better results than RANS in curved open-channel turbulent flows. An additional advantage is that using LES it is possible to obtain further physical insights from the computed data.…”
Section: Introductionmentioning
confidence: 99%
“…The subgrid-scale (SGS) stresses, resulting from the unresolved motions, are modelled using the Smagorinsky subgrid-scale model (Smagorinsky, 1963) with a model constant C s of 0.1. Such an approach has been used successfully for similar flows by Hinterberger et al (2007) and Moncho-Esteve et al (2017). For flows without homogeneous directions, as the present one, the Smagorinsky model is more robust than other models like the dynamic Smagorinsky which require some kind of smoothing of the model parameter (like time relaxation).…”
Section: Methodsmentioning
confidence: 74%
“…Capítulo 5. A Numerical Study of the Complex Flow Structure in a Compound Meandering Channel secondary motions and its influence on the streamwise velocity distribution as well as on mixing are summarised in Blanckaert and Graf (2004), Blanckaert (2009) and Moncho-Esteve et al (2017). Moreover, river flows in a compound channel often inundate the adjacent plains, which generate more complicated flow structures between the in-bank and the floodplain flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation